Diagnosis of deep vein thrombosis with D-dimer adjusted to clinical probability: prospective diagnostic management study. (15th February 2022) - Kearon, Clive; de Wit, Kerstin; Parpia, Sameer; Schulman, Sam; Spencer, Frederick A; Sharma, Sangita; Afilalo, Marc; Kahn, Susan R; Le Gal, Gregoire; Shivakumar, Sudeep; Bates, Shannon M; Wu, Cynthia; et al.
Abstract: Objective: To evaluate the safety and efficiency of a diagnostic algorithm for deep vein thrombosis (DVT) that uses clinical pretest probability based D-dimer thresholds to exclude DVT. Design: Prospective diagnostic management study. Setting: University based emergency departments or outpatient clinics in Canada. Participants: Patients with symptoms or signs of DVT. Intervention: DVT was considered excluded without further testing by Wells low clinical pretest probability and D-dimer <1000 ng/mL or Wells moderate clinical pretest probability and D-dimer <500 ng/mL. All other patients had proximal ultrasound imaging. Repeat proximal ultrasonography was restricted to patients with initially negative ultrasonography, low or moderate clinical pretest probability, and D-dimer >3000 ng/mL or high clinical pretest probability and D-dimer >1500 ng/mL. If DVT was not diagnosed, patients did not receive anticoagulant treatment. Main outcome measure: Symptomatic venous thromboembolism at three months. Results: 1508 patients were enrolled and analysed, of whom 173 (11.5%) had DVT on scheduled diagnostic testing. Of the 1275 patients with no proximal DVT on scheduled testing who did not receive anticoagulant treatment, eight (0.6%, 95% confidence interval 0.3% to 1.2%) were found to have venous thromboembolism during follow-up. Compared with a traditional DVT testing strategy, this diagnostic approach reduced the need for ultrasonography from a mean of 1.36 scans/patient to 0.72 scans/patient (difference −0.64, 95% confidence interval −0.68 to −0.60), corresponding to a relative reduction of 47%. Conclusions: The diagnostic strategy using a combination of clinical pretest probability and D-dimer identified a group of patients at low risk for DVT during follow-up while substantially reducing the need for ultrasound imaging. Registration: ClinicalTrials.gov NCT02038530 .